Stress urinary incontinence in physically active women – current evidence, risk factors and clinical relevance - Ściążko-Gancarczyk, Sabina; Gancarczyk, Maciej; Węgrzyn, Jagoda (Journal of Education, Health and Sport, 2025)
Background: Stress urinary incontinence (SUI) affects many women, including those who are physically active. Although traditionally linked to childbirth, menopause, and obesity, recent research shows that SUI is also common in young, nulliparous athletes without classic risk factors. Objective: To summarize current evidence on epidemiology, mechanisms, risk factors, diagnostics, and management of SUI in physically active women. Methods: A narrative review of studies published between 2000–2024 was performed using PubMed, Scopus, and Google Scholar. Included were observational and experimental studies, systematic reviews, meta-analyses, and guideline documents. Results: Prevalence of SUI in athletes often exceeds that in the general female population, reaching 50–60% in high-impact sports. Pathophysiology involves repetitive mechanical loading, increased intra-abdominal pressure, impaired pelvic floor muscle activation, and—occasionally—hormonal or energy-availability disturbances. Diagnostics follow standard protocols, with emphasis on sport-specific history and pelvic floor evaluation. First-line management is pelvic floor muscle training integrated with motor control and breathing retraining. Surgical treatment is considered only for symptoms refractory to conservative therapy. Conclusions: SUI is common yet underrecognized among physically active women. Effective management requires early identification, targeted diagnostics, and individualized conservative treatment. Further research is needed on sport-specific mechanisms and long-term outcomes.